The Influence of Mother’s Characteristics Toward Basic Complete Immunization Non-Compliance for Children Under-Two-Years - Riska Harmasdiyani (Jurnal Berkala Epidemiologi, 2015)
Mothers have an important role in determining the health status of children. Measurement of compliance with complete basic immunization is used to assess the extent of complete basic immunization. This study aims to determine the effect of maternal characteristics on non-compliance with complete basic immunization in under two years. This research is an observational analytic study with case-control research design. The sample in this study consisted of 49 respondents in each case group and the control group with a cluster random sampling technique. Significant variables in this study were calculated using logistic regression analysis and the magnitude of the risk was calculated using an odds ratio. The results showed that the mother's education and knowledge had a risk of non-compliance with complete basic immunization. A low level of education has a risk of 9,281 times the non-compliance with complete basic immunization compared to tertiary education. Mother's knowledge is 20.9 times less risky of non-compliance with complete basic immunization than good knowledge. Lack of maternal knowledge and low maternal education affect the failure to provide complete basic immunization. Suggestions from this research are to increase the presence of mothers to Integrated health care post and the need to increase the role of health workers through Educational Information Communication activities to increase maternal knowledge.